Study of Gall bladder contractility in patients of asymptomatic Gall stone - Dugar, Dharmendra; Khadanga, Sagar; Houghton T, Tim; Ghata, Swarupjit; Satapathy, Shakti (International Journal of Medical Research and Review, 2014)
Introduction: The prevalence of gall bladder stone varies widely in different parts of world. Worldwide gall stone disease is increasing. A knowledge of the predictive factors of the development and persistence of symptoms in gall stone patients play a key role in clinical decision making. The aim of this study is to evaluate the presence of predictive factors for biliary pain development in gall stone, stressing the role of gall bladder motility. Aims and objective: To study gall bladder contractility in patients of asymptomatic gall stone by ultrasound and to correlate with normal individuals. Material and methods: A hospital based observational study was conducted from January 2012 to march 2013. A total of 25 patients with asymptomatic gall stones (group 1) and 25 controls (group 2) were included in the study. Results: Ultrasonography volume was found to be significantly more in group 1, both during fasting and after fatty meals, suggesting decreased gall bladder motility in asymptomatic patient. Inter group comparison of gall bladder thickness was statistically significant both during fasting and after fatty meal in group. Conclusion: Gall bladder volume was found to be significantly more in asymptomatic cases, both during fasting and after fatty meal. Mean gall bladder wall thickness and mean alkaline phosphatase level was significantly more in patients with gall stones.